Human-Crocodile Conflicts in Sarawak, Malaysian Borneo: An analysis of crocodile attacks from 2000 until 2020 - Mohd Izwan Zulaini, Abdul Gani; Ruhana, Hassan; Tisen, Oswald Braken; Rambli, Ahmad (2022)
Crocodiles have caused a relatively high number of fatalities towards local people in Sarawak, a Malaysian state in Borneo. However, they have important cultural values and are well respected by the riverine communities in the state. The objective of this study is to determine the patterns of human-crocodile conflict in Sarawak which could help in managing the problems between crocodile and human. Information on crocodile attacks were collected from multiple sources including records kept by local authority, media or CrocBITE database. Over a 21 years period (year 2000-2020), the record attacks (n=164) showed a balance between fatal and non-fatal cases. Most common victims in Sarawak were male (86.6%) and adults from the age of 31 to 40 years old (20.7%). The attacks occurred more during the daylight (59.4%), with the peak time for crocodile attacks was approximately between 1800 to 2359 hours (33.3%). Crocodile attacks occur slightly more during the wet season, from October to March (54.0%), with the highest one recorded in March (16.8%). Fishing (26.2%) and bathing (22.0%) in the rivers possess the highest risk of crocodile attack, suggesting that crocodiles are more likely to attack when the victim is in the water. The findings imply that crocodiles' attack pattern in Sarawak is associated with the people’s activities pattern. There is a need to update the database on crocodile attacks in Sarawak on -real time basis as this will facilitate the relevant agencies in formulating the strategies to reduce the number of crocodile attacks and ensuring the safety of the riverine communities.